MAGMA CHAMBERS BENEATH THE KLYUCHEVSKOY VOLCANIC GROUP - Khubunaya S.A.; Gontovaya L.I.; Sobolev A.V.; Nizkous I.V. (My University, 2007)
A 3D velocity model of the Earth's crust beneath the Klyuchevskoy volcanic group has been constructed using the seismic tomography method. Anomalies of the velocity parameters related to the zones of magma supply to active volcanoes have been distinguished. Petrological data on the composition, temperature, and pressure of generation and crystallization of primary melts of Klyuchevskoy volcano magnesian basalts have been obtained. The primary melt corresponds to picrite (MgO = 13-14 wt %) with an ultimate saturation of SiO2 (49-50 wt %), a high H2O content (2.2-2.9%), and incompatible elements (Sr, Rb, Ba, Hf). This melt is formed at pressures of 15-20 kbar and temperatures of 1280--1320С . Its further crystallization proceeds in intermediate magma chambers at two discrete pressure levels (i.e., greater than 6, and 1-2 kbar). The results of the petrological studies are in good agreement with the seismotomographic model.
Keywords: 38.37.19 Магматизм и магматические горные породы; 38.37.25 Вулканология; Ключевской; 550.34, 552.321.6+552.335